The Longitudinal Relationship between Peer Violence and Popularity and Delinquency in Adolescent Boys: Examining Effects by Family Functioning - Henneberger, Angela K. (2012)
Mapping the relationship of peer influences and parental/family characteristics on delinquency can help expand the understanding of findings that show an interdependence between peer and family predictors. This study explored the longitudinal relationship between two characteristics of peer relationships (violence and perceived popularity) with subsequent individual delinquency and the moderating role of family characteristics (cohesion and parental monitoring) using data from the Chicago Youth Development Study. Participants were 364 inner-city residing adolescent boys (54% African American; 40% Hispanic). After controlling for the effects of age and ethnicity, peer violence is positively related to boys’ delinquency. The effect of popularity depends on parental monitoring, such that the relationship between popularity and delinquency is positive when parental monitoring is low, but there is no relationship when parental monitoring is high. Furthermore, parental monitoring contributes to the relationship between peer violence and delinquency such that there is a stronger relationship when parental monitoring is low. Additionally, there is a stronger relationship between peer violence and delinquency for boys from high cohesive families. Findings point to the value of attention to multiple aspects of peer and family relationships in explaining and intervening in the risk for delinquency. Furthermore, findings indicate the importance of family-focused interventions in preventing delinquency.